CONTROLLING CANNIBALISM OF ASIAN REDTAIL CATFISH (Hemibagrus nemurus) LARVAE USING PASTE FEED SUPPLEMENTED WITH TURMERIC FLOUR - Yulindra, Ade; Benny Heltonika; Netti Aryani (Asian Journal of Aquatic Sciences, 2025)
Cannibalism is a significant issue during the early stages of Asian redtail catfish (Hemibagrus nemurus) culture, as it negatively affects survival rates. This study aimed to investigate of turmeric (Curcuma longa) flour supplementation in pasta feed to control cannibalism in Asian redtail catfish larvae and the potential to replace silk worm as a feed. A completely randomized design (CRD) was employed, consisting of five treatment groups with four replications each. The larvae were fed pasta diets supplemented with varying doses of turmeric flour (0, 5, 10, and 15 mg/kg), along with a comparative feed using Tubifex sp. The parameters assessed included cannibalism rate, survival rate, and growth performance. The results showed that the highest survival rate (93.33 ± 1.33%) and lowest cannibalism index (2.67 ± 0.94%) were observed in the group fed Tubifex sp. The highest weight gain (24.22 ± 0.53 g) and specific growth rate (9.35 ± 0.03%) were also recorded in this group. However, supplementation of turmeric flour at a dosage of 15 mg/kg in pasta feed was able to reduce cannibalism and improve the growth of Asian redtail catfish larvae. This treatment resulted in a cannibalism index of 11% and a survival rate of 82.67%. In terms of growth performance, larvae under this treatment exhibited a weight gain of 6.13 g, a length gain of 3.58 cm, a specific growth rate (SGR) of 6.07%/day, and a particular growth rate of length (SLR) of 4.25%/day. Pasta feed supplemented with 15 mg/kg turmeric flour can serve as an alternative to replace silk worms, achieving 25% of their weight gain and 63% of their length gain.